ETYMOLOGICAL ORIGIN OF THE LEXEME OF “PROPERTY” IN ENGLISH AND ITS MORPHOLOGICAL, LEXICAL AND SEMANTIC FEATURES - Shokirova Diloramkhon Abduvali qizi (Scholar Express Journals, 2022)
There are a simple and complex structure in concepts. There is more semantic meaning in simple concepts and are less dependent on the lifestyle of the people. They have their own lexical meaning in all languages and can be included in the category of lexical universals. Complex concepts can be thought of as a long-standing process of the people speaking the same language - a concept is formed on the basis of the way of life of the people, for example, a concept is formed on the basis of idiomatic phraseological combinations
Keywords: Simple And Complex Concepts; Lexical Meaning; Lexical Universality; Phraseological Combination